Penyitaan Aset dengan Pendekatan Berbasis Nilai Terhadap Aset Pelaku Tindak Pidana Korupsi - Aurora Tifani Suci; Yana Indawati (Jurnal Hukum Lex Generalis, 2025)
There are several problems that arise in the handling of criminal corruption cases, namely related to the confiscation of assets, one of which is the investigator's obligation to prove the relationship between assets and criminal acts of corruption. Failure to prove this relationship could result in the absence of assets that can be confiscated to cover state financial losses. So it is felt necessary to look for another confiscation system that can be implemented effectively in recovering state financial losses. The research was carried out using a Normative-Empirical research type conceptual and statutory approach. The results of the research are that there is a concept that can overcome the problems in confiscation listed in Article 31 UNCAC 2003, namely value-based system. This confiscation system can confiscate all assets belonging to the suspect as replacement assets without having to first prove the connection between the assets and the criminal act of corruption.